Prognostic value of body mass index in the development of cardiovascular diseases among Kaunas male population - Tamosiũnas, A; Domarkiene, S; Reklaitiene, R; Jureniene, K; Varanauskiene, Z; Janusauskas, A (Cor et vasa, 1992)
The paper presents the results of a primary medical examination and of a prospective, on the average 14-year follow-up study of the male population of Kaunas aged 45-59 years (n = 2452). The prevalence of overweight, according to the WHO criteria, was 48.7%, that of obesity 20.5%. With increasing body mass index (BMI) there occurred a statistically significant increase of main risk factors of ischaemic heart disease (IHD) and of IHD itself. The results of the prospective study showed a U-shaped relationship between BMI and mortality from all cardiovascular diseases, and a J-shaped relationship between BMI and mortality from IHD and morbidity of acute myocardial infarction, respectively. The same relationship held true even after standardization of the level of all other risk factors using the multiple logistic function. Thus, the overweight was confirmed as an independent IHD risk factor in the given population.
Keywords: rizikové faktory; Cardiovascular Diseases; Myocardial Ischemia; Litva; Male; longitudinální studie; prognóza; Middle Aged; Longitudinal Studies; infarkt myokardu; Prospective Studies; Prognosis; Myocardial Infarction; mužské pohlaví; ischemická choroba srdeční; index tělesné hmotnosti; Adult; Risk Factors; Lithuania; Body Mass Index; Obesity; dospělí; lidé středního věku; kardiovaskulární nemoci; prospektivní studie; obezita; Prevalence; lidé; Humans; prevalence